Guru Honorer dan Stagnasi Mutu Pendidikan Indonesia dalam Perspektif Sejarah (1900-2026) - Kurniawan; Siti Fatimah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
The honorary teacher crisis in Indonesia has been ongoing for decades without a fundamental solution. This article aims to analyze the historical-structural roots of the honorary teacher problem and its correlation with the stagnation of national education quality. This research employs historical methods with a qualitative approach through four stages: heuristics, source criticism, interpretation, and historiography. The theoretical frameworks used are Fernand Braudel's longue durée, Pierre Bourdieu's social reproduction, and Paulo Freire's critical pedagogy. The results show that the honorary teacher crisis is not merely a technical failure in implementing Law Number 14 of 2005 concerning Teachers and Lecturers, but an accumulation of three layers of structural inheritance: discriminatory dualism from the colonial era, the "black pedagogy" of the New Order that suppressed teacher professional initiative, and governance fragmentation due to post-reform decentralization. Based on 2025 Ministry of Education data, there are 2.6 million honorary teachers (56% of all teachers) with incentives of only Rp400,000 per month in 2026, while Indonesia's 2022 PISA scores (359 reading, 366 mathematics) are the lowest in history. This study concludes that resolving the teacher crisis requires fundamental restructuring of teacher governance, not merely piecemeal policy adjustments. The contribution of this research is to provide a comprehensive historical-structural analysis of the honorary teacher problem in Indonesia.